Immunoregulatory paracrine effect of mesenchymal stem cells and mechanism in the treatment of osteoarthritis - Zhang, Xiuzhi; Liu, Tianhao; Ran, Chunxiao; Wang, Weidan; Piao, Fengyuan; Yang, Jiahui; Tian, Simiao; Li, Lu; Zhao, Dewei (Frontiers in Cell and Developmental Biology, 2024)
Osteoarthritis (OA) is a degenerative joint disease caused by chronic inflammation that damages articular cartilage. At present, the treatment of OA includes drug therapy to relieve symptoms and joint replacement therapy for advanced OA. However, these palliatives cannot truly block the progression of the disease from the immunological pathogenesis of OA. In recent years, bone marrow mesenchymal stem cell (BMSC) transplantation has shown great potential in tissue engineering repair. In addition, many studies have shown that BMSC paracrine signals play an important role in the treatment of OA through immune regulation and suppressing inflammation. At present, the mechanism of inflammation-induced OA and the use of BMSC transplantation in joint repair have been reviewed, but the mechanism and significance of BMSC paracrine signals in the treatment of OA have not been fully reviewed. Therefore, this article focused on the latest research progress on the paracrine effects of BMSCs in the treatment of OA and the related mechanisms by which BMSCs secrete cytokines to inhibit the inflammatory response, regulate immune balance, and promote cell proliferation and differentiation. In addition, the application potential of BMSC-Exos as a new type of cell-free therapy for OA is described. This review aimed to provide systematic theoretical support for the clinical application of BMSC transplantation in the treatment of OA.